Hydrogels Embedded With Melittin and Tobramycin Are Effective Against Pseudomonas aeruginosa Biofilms in an Animal Wound Model - Maiden, Michael M.; Zachos, Mitchell P.; Waters, Christopher M. (Frontiers in Microbiology, 2019)
We demonstrate that the antimicrobial peptide, melittin, is effective alone and in combination with the aminoglycosides tobramycin to kill Pseudomonas aeruginosa growing as biofilms both in vitro and in vivo. Melittin and tobramycin show enhanced in vitro activity in combination at micromolar concentrations, resulting in a 2-log10 reduction in the number of cells within mature PAO1 P. aeruginosa biofilms after 6-h of treatment. Alternatively, either agent alone resulted in half-a-log10 reduction. Time-killing assays demonstrated that the combination of melittin and tobramycin was effective at 2-h whereas tobramycin was not effective until after 6-h of treatment. We also found the combination was more effective than tobramycin alone against biofilms of 7 P. aeruginosa cystic fibrosis clinical isolates, resulting in a maximum 1.5-log10 cellular reduction. Additionally, melittin alone was effective at killing biofilms of 4 Staphylococcus aureus isolates, resulting in a maximum 2-log10 cellular reduction. Finally, melittin in combination with tobramycin embedded in an agarose-based hydrogel resulted in a 4-fold reduction in bioluminescent P. aeruginosa colonizing mouse wounds by 4-h. In contrast, tobramycin or melittin treatment alone did not cause a statistically significant reduction in bioluminescence. These data demonstrate that melittin in combination with tobramycin embedded in a hydrogel is a potential treatment for biofilm-associated wound infections.